Financial Management Challenges Facing Implementation of Free Day Secondary Education In Imenti North District,Kenya - Kaguri, Ngatu Beatrice; Kaguri Ngatu Beatrice (Meru: Kaguri Ngatu Beatrice, 2014)
Almost all modern organizations, including schools have the characteristics of the five basic functions performed by all managers which are planning, organizing, commanding, coordinating and controlling. The launch of Free Primary Education (FPE) in Kenya in 2003 led to increased number of students attending and completing primarry school. This placed intense pressure for the government to meet the growth demand for secondary education. Due to low transition rate of students from primary school to secondary school, the government of Kenya launched Free Secondary Education (FSE) initiative strategy in 2008. FSE was started to increase the transition percentage rate of students from primary to secondary schools,retention and completion without any discrimination.The purpose of this study therefore was to investigate financial , management challenges facing implementation of Free Day Secondary Education(FDSE)) in Imenti North District, Meru County, Meru County ,Kenya in relation to the role of financial, planning, reports, and controls.This study adopted Henri Fayol principles of management which its concepts and principles are common in situations of educational administration in kenya. The sampling design adopted for this research was simple random sampling. Stratified sampling was used to select the principles,BOGs and PTAs while the District Education Officer (DEO) and Zonal Quality Assurance and Standards Officer (ZQASOs) were censured .Questionnaires were used as instruments for collecting data from the BOGs and PTAs while interview schedules were administered to the Principals, DEO and ZQASOs.Validity of the instruments was done through expert researchers. Reliability was tested through split- half technique and a reliability coefficient computed through the use of Spearman Brown Prophecy Formula. The collected data was analyzed using descriptive statistics method of data cleaning and coding. Results of data collected show that Free Day Secondary Schools continue to charge fees for lunch, school unidorms and transport for their children. This project concluded that Free Day Secondary Education has not been able to achieve its objectives due to a variety of variables and gave recommendations for improvements based on the finding and discussions.
A Research thesis submitted in partial fulfillment of the requirement for the award of the degree of masters of Business Administration in strategic management in the school of Business and Economics of Meru University of Science and Technology